Perisai ke-aswaja-an Nahdlatul Wathan : membedah 17 literatur anti wahabi rekomendasi pendiri NW / H. Abdul Aziz Sukarnawadi - ABDUL AZIZ SUKARNAWADI, H., 1984- (Samudra biru, 2016)
xviii, 124 hlm. : ilus. ; 18 cm.